Structural Factors, Unemployment and Monetary Policy: The Useful Role of the Natural Rate of Interest - Francesco Furlanetto; Paolo Gelain (Norges Bank, 2016)
We study the role of monetary policy in response to variations in unemployment due to structural factors, modeled as exogenous changes in matching efficiency and in the size of the labor force. We find that monetary policy should play a role in such a scenario. Both negative shocks to the matching efficiency and negative shocks to the labor force increase inflation, thus calling for an increase in the interest rate when policy is conducted following Taylor-type rules. However, the natural rate of interest declines in response to both shocks. The optimal Ramsey policy prescribes small deviations from price stability and lowers the interest rate, thus tracking the natural rate of interest in response to both shocks. Structural factors in the labor market may have contributed to the recent decline in the natural rate of interest in the US.
hdl:11250/2495711
Keywords: E32; 330; Taylor rule; optimal monetary policy; natural rate of interest; natural rate of unemployment; labor force shocks